2004
DOI: 10.1007/s00418-004-0634-8
|View full text |Cite
|
Sign up to set email alerts
|

Replica immunoelectron microscopic study of the upper surface layer in rat mandibular condylar cartilage by a quick-freezing method

Abstract: A quick-freezing and deep-etching method in combination with replica immunoelectron microscopy was applied for examining localization of hyaluronic acid and fibronectin on the upper surface layer of rat mandibular condylar cartilage. Rat temporomandibular joints were dissected with articular disks in order to leave the articular cartilage surface intact. The disks were slightly cut with razor blades for exposing the condylar articular cartilage surface. They were quickly frozen with the isopentane-propane cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
(13 reference statements)
0
12
0
1
Order By: Relevance
“…93 Cells and fibrils appeared embedded in a matrix that we tentatively categorized as fibronectin-like (Fig. 11), based on its similarity to QFDE images of Zea-Aragon et al, 94 who identified similar structures via immunogold. Qualitatively, our QFDE image library showed that more of this fibronectin-like matrix was present in the 1% ITS þ 1% FBS culture (not shown).…”
Section: Ecm Structuresmentioning
confidence: 89%
“…93 Cells and fibrils appeared embedded in a matrix that we tentatively categorized as fibronectin-like (Fig. 11), based on its similarity to QFDE images of Zea-Aragon et al, 94 who identified similar structures via immunogold. Qualitatively, our QFDE image library showed that more of this fibronectin-like matrix was present in the 1% ITS þ 1% FBS culture (not shown).…”
Section: Ecm Structuresmentioning
confidence: 89%
“…At an electron microscopic level, when the cryotechnique is combined with the freeze-fracture replica method as described in the previous section (Section II), we recently reported that the cryotechnique is applicable for the in situ immunolocalization of some soluble matrix molecules, such as hyaluronic acid and fibronectin, in the rat mandibular joint cartilage [20]. Therefore, we have now proposed that the quick-freeze replica method can maintain the original distribution of all biological molecules in cells and tissues by sealing them in a vitreous ice crystal environment.…”
Section: Preservation Of Soluble Components With the In Vivo Crymentioning
confidence: 99%
“…This technique was performed by rapid freezing of these tissues with liquid isopentane-propane cryogen (À1938C) with or without cutting using a cryoknife (À1968C) cooled down in liquid nitrogen. In previous studies, the dynamic morphological changes in living cells, tissues, and organs using the cryotechnique were observed by electron and light microscopy (Ohno et al, 1996;Takayama et al, 1999Takayama et al, , 2000Terada et al, 1998;Xue et al, 2001;Zea-Aragon et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%